Development of STEM-Based Assemblr EDU Learning Media toImprove Students' Creative Thinking Skills and Performance - Prakosa, Ilham Panca; Yanuarto, Wanda Nugroho (Universitas Islam Negeri Raden Intan Lampung, 2026)
The increasing emphasis on twenty-first century competencies has intensified the need for mathematics learning environments that promote creative thinking, conceptual exploration, and active student engagement. Nevertheless, mathematics instruction in many secondary schools continues to rely heavily on procedural and teacher-centered approaches, limiting students’ opportunities to develop flexible and original mathematical reasoning. Although augmented reality (AR) has shown promising potential in educational contexts, existing studies have predominantly focused on learning motivation and academic achievement, while the development of creative mathematical cognition within immersive STEM-oriented environments remains insufficiently explored. This study aimed to develop STEM-based Assemblr EDU learning media and examine its validity, practicality, and effectiveness in improving students’ creative thinking skills and classroom performance in trigonometry learning. The study employed a Research and Development approach integrated with a quasi-experimental design using the ADDIE model. The participants consisted of 60 tenth-grade students at SMA Muhammadiyah Tambak, Indonesia, divided into experimental and control classes. Data were collected through creative thinking tests, classroom observations, interviews, validation sheets, and student response questionnaires. The developed media achieved a validity score of 83.16% and a practicality percentage of 90.6%, indicating high feasibility for classroom implementation. Inferential analysis using the Mann–Whitney U test revealed a statistically significant difference between groups (p < .001), while the experimental class achieved a moderate N-Gain score (0.37) and a large effect size (d = 0.59). Qualitative findings additionally demonstrated increased participation, collaborative interaction, and confidence during learning activities. These findings suggest that immersive AR-supported STEM learning can function as a transformative pedagogical environment that fosters meaningful, exploratory, and creativity-oriented mathematics learning in contemporary secondary education